Triglyceride-Glucose Index Is Related to Carotid Plaque and Its Stability in Nondiabetic Adults: A Cross-Sectional Study - Wang, Anran; Li, Yapeng; Zhou, Lue; Liu, Kai; Li, Shaohua; Song, Bo; Gao, Yuan; Li, Yusheng; Lu, Jie; Tian, Chuansheng; Xu, Yuming; Wang, Longde (Frontiers in Neurology, 2022)
Background Carotid plaque plays an important role in the development of stroke. The triglyceride-glucose (TyG) index is a reliable alternative marker of insulin resistance. However, there are limited data regarding the relationship between TyG index and carotid plaque and its stability in nondiabetic adults. Methods This study was carried out on 24,895 urban workers (10,978 men and 13,917 women) aged 20 years or older who participated in a comprehensive health screening between January 2016 and December 2017 at the First Affiliated Hospital of Zhengzhou University, China. Carotid plaque was assessed using ultrasonography. TyG index was calculated as ln [fasting triglyceride (mg/dL) × fasting glucose (mg/dL) /2]. Logistic regression models and restricted cubic spline (RCS) models were used to estimate the association of the TyG index with carotid plaque and its stability by odds ratios (ORs) and 95% confidence intervals (CIs). Results Carotid plaque was detected in 5,668 (22.8%) respondents, with stable and unstable plaque accounting for 2,511 (10.1%) and 3,158 (12.7%), respectively. There was a significant positive association between the prevalence of carotid plaque and TyG index quartile levels, and the same associations were observed for the prevalence of stable and unstable carotid plaque (P for trend <0.0001). The multivariable-adjusted ORs (95% CIs) for the highest vs. lowest quartile of TyG index were 1.30 (1.15–1.47) for carotid plaque, 1.38 (1.17–1.63) for stable carotid plaque, and 1.24 (1.07–1.43) for unstable carotid plaque. The RCS analysis showed a linear association between TyG index and carotid plaque, and linear associations were also observed between TyG index and both stable carotid plaque and unstable carotid plaque (P for linearity<0.05). Conclusion Our findings suggested that the TyG index was significantly associated with carotid plaque and might be a useful indicator for the early identification of carotid plaque in nondiabetic subjects.